Mental health support group in primary health care: an experience report - Franco, Renato Soleiman (2024)
Problem: Among the challenges faced in the mental disorders field in Brazil, it is pertinent to highlight the scarcity of resources and services, their integration, and the stigma surrounding mental illness. Despite the difficulties, some significant progress is being achieved in this care such as group interventions in primary health care. Methods: The implementation of a therapeutic group in a Health Center is described and analyzed in this experience report, aiming at contributing to the enrichment of collective intervention in patients with mental health complaints. The aim was to work together with patients complaining about anxiety or depression after analyzing a great demand in the area for this care. Results: After two months of weekly meetings, we could go beyond the conventional practices offered in groups, providing the health teams with the opportunity to reflect on alternatives to promote changes in the forms of mental health care. Conclusions: In addition to stimulating the exchange of knowledge between university students, professionals, and the community, the implementation of therapeutic groups showed to be promising in the care of mental disorders and as a psychosocial rehabilitation method in primary health care.